COMMUNITY CAPACITY IN DEALING WITH DROUGHT IN INSANA BARAT DISTRICT, NORTH CENTRAL TIMOR, EAST NUSA TENGGARA - Sanit, Maria Serlince; Rachmawati, Turniningtyas Ayu; Firdausiyah, Nailah (Directorate of Research and Community Service (DRPM), 2022)
Insana Barat Subdistrict is an area in North Central Timor Regency which is vulnerable to the dry season every year and experiences a water deficit. To reduce the risk of drought, community preparedness needs to be improved through the provision of water to deal with drought. Several efforts have been made by the government and the community to cope with drought, including the construction of dams, distribution of clean water fiber, and the existence of cropping patterns in agriculture. This study aims to determine the capacity of the people of Insana Barat District in dealing with drought. The role of the community becomes very important because in fact the community and local organizations are the key in disaster risk reduction initiatives. The method used in this research is quantitative with a survey in Insana Barat District with 335 respondents spread over each village. Determination of respondents in this study was done randomly. The analysis technique used is scoring and capacity calculation using the asset pentagon on the variables of human assets, social assets, natural assets, physical assets and financial/financial assets. The results showed that the people in Usapinonot Village, Unini Village, Letneo Village, Banae Village, Nifunenas Village, Subun Tualele Village, Subun Bestobe Village belonged to low capacity, Subun Village, Lapeom Village, Atmen Village and South Letneo Village were classified as medium capacity. and Oabikasi Village is included in the high classification.